Halal Tourism As A Driver Of Sustainable Destination Development In Asean: Evidence From Indonesia, Malaysia, And Thailand - Al Maulud; Ismail (IQTISHADUNA: Jurnal Ekonomi dan Keuangan Islam, 2026)
Halal tourism has emerged as an important strategy for promoting sustainable destination development in ASEAN, yet comparative evidence on how it contributes to sustainability across different national contexts remains limited. This study examines the role of halal tourism in supporting sustainable destination development in Indonesia, Malaysia, and Thailand, with particular attention to the contribution of Digital Business Models for Sustainability (DBMS). Using a comparative qualitative content analysis of secondary data from Our World in Data, the study analyzes three indicators: international tourism expenditure, sustainable tourism monitoring capacity, and tourism’s contribution to gross domestic product. The findings reveal distinct development patterns across the three countries. Malaysia demonstrates the strongest institutional integration between halal tourism, sustainability governance, and digital support systems. Thailand exhibits a highly adaptive halal-friendly tourism model characterized by strong economic dependence on tourism and expanding sustainability monitoring mechanisms. Indonesia shows steady growth and significant potential but remains in a consolidation phase marked by uneven governance and monitoring capacity. These findings suggest that the effectiveness of halal tourism as a driver of sustainable destination development depends not only on market growth but also on the integration of digital governance, sustainability monitoring, and institutional capacity. This study contributes to the literature by providing a comparative ASEAN perspective that links halal tourism, sustainable destination development, and DBMS within a unified analytical framework.